2018
DOI: 10.3389/fmolb.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effects of Berberine and Sanguinarine

Abstract: Berberine and Sanguinarine alkaloids belong to a group of naturally occurring chemical compounds that mostly contain basic nitrogen atoms. This group also includes some related compounds with neutral or weakly acidic properties. Alkaloids are produced by a large number of organisms including bacteria, fungi, plants, and animals. Berberine and Sanguinarine both are isoquinoline derivatives and belong to protoberberine and benzophenanthridines, respectively. Tyrosine or phenylalanine is common precursor for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 50 publications
(60 reference statements)
5
100
0
9
Order By: Relevance
“…Medicinal plants, which are the basis of traditional medicine in various countries, have been investigated for their pharmacological properties and have revealed numerous significant novel phytochemicals with the potential to treat and manage diseases 10 . This includes the discovery of paclitaxel (Taxol), an anticancer drug discovered from the bark of the Himalayan Yew tree 11 ; berberine isoquinoline alkaloid an antineoplastic, antidiabetic drug found in plants belonging to Berberidaceae family 12 , and Artemisinin, an antimalaria drug derived from Artemisia annua 13 , to mention a few. In recent studies, plants and their constituents have shown significant potential as therapeutic agents for oxidative stress and include polyphenolic compounds such as resveratrol, gallic acid, catechin, quercetin, kaempferol, and several anthocyanins from grapes skin 14 .…”
mentioning
confidence: 99%
“…Medicinal plants, which are the basis of traditional medicine in various countries, have been investigated for their pharmacological properties and have revealed numerous significant novel phytochemicals with the potential to treat and manage diseases 10 . This includes the discovery of paclitaxel (Taxol), an anticancer drug discovered from the bark of the Himalayan Yew tree 11 ; berberine isoquinoline alkaloid an antineoplastic, antidiabetic drug found in plants belonging to Berberidaceae family 12 , and Artemisinin, an antimalaria drug derived from Artemisia annua 13 , to mention a few. In recent studies, plants and their constituents have shown significant potential as therapeutic agents for oxidative stress and include polyphenolic compounds such as resveratrol, gallic acid, catechin, quercetin, kaempferol, and several anthocyanins from grapes skin 14 .…”
mentioning
confidence: 99%
“…However, the encapsulation efficiency of BER in these liposomes was very low (2%, Table 2 ), probably due to the electrostatic repulsions between the positively charged BER molecule and the cationic lipid DDAB, which led us to discard this liposomes composition. DP was used for the preparation of anionic liposomes as the previously reported strong affinity of BER by phosphate groups [ 46 ] could increase its encapsulation. Although a higher encapsulation efficiency was reached (28.7%, Table 2 ), PC:Chol:DP-BER showed much higher toxicity than PC:Chol:TS-BER (>7-fold, Table 3 ) and similar to free BER, as well as higher size compared to PC:Chol:TS-BER (122 vs 245 nm, Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of pharmacological properties and effects have been reported, such as antimalarial (eg, quinine), antiasthma (eg, ephedrine), anticancer (eg, homoharringtonine), cholinomimetic (eg, galantamine), vasodilatory (eg, vincristine), antiarrhythmic (eg, quinidine), analgesic (eg, morphine), antibacterial (eg, chelerythrine), and antihyperglycemic activities (eg, vincristine and vinblastine). 16 SAN [13-methyl-(1,3) benzodioxolo-(5,6-C)-1,3-dioxolo(4,5)-phenanthrene] is the most widely used benzophenanthridine alkaloid, which originates from the Canadian Haemorrhoa and other Papaver plants, 17 and has antimicrobial, antioxidant and anti-inflammatory properties. 18 SAN is a low toxicity, safe alkaloid and is relatively specific for cancer cells; 19,20 it has been approved with known safety and bioavailability by the Food and Drug Administration (FDA) and included in the Prestwick Chemical Library.…”
Section: Discussionmentioning
confidence: 99%